2019
DOI: 10.13057/biodiv/d210113
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics resistant Escherichia coli isolated from aquatic ecosystems in Palembang, South Sumatra, Indonesia

Abstract: Abstract. Verawaty M, Apriyani N, Tarigan LR, Apriyan ET, Laurenta WC, Apriani N, Muharani. 2020. Antibiotics resistant Escherichia coli isolated from aquatic ecosystems in Palembang, South Sumatra, Indonesia. Biodiversitas 21: 86-97. Antibiotics-resistant bacteria (ARB) are one of the emerging water contaminants currently gaining serious global concern due to their adverse risk to ecosystems, wildlife, and public health. This study determined antibiotics resistant Escherichia coli isolated from aquatic ecosys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In Bogor, Indonesia, nearly all E. coli was amoxicillin and erythromycin-resistant [64]. Similarly, E. coli is resistant to penicillin in an aquatic environment in another location in Indonesia (Sumatra) [74]. A similar result was obtained in New Deli in India, where high levels of ARGs associated with resistance to TC, sulfonamide, and β-lactam were detected in all stages in WWTP [65].…”
Section: Bacterial Resistance To Antimicrobialsmentioning
confidence: 74%
“…In Bogor, Indonesia, nearly all E. coli was amoxicillin and erythromycin-resistant [64]. Similarly, E. coli is resistant to penicillin in an aquatic environment in another location in Indonesia (Sumatra) [74]. A similar result was obtained in New Deli in India, where high levels of ARGs associated with resistance to TC, sulfonamide, and β-lactam were detected in all stages in WWTP [65].…”
Section: Bacterial Resistance To Antimicrobialsmentioning
confidence: 74%
“…Reports on resistant bacteria are still very limited in Indonesia. Verawaty et al (2020) reported the presence of E. coli that is resistant to ampicillin, tobramycin, and tetracycline in the waters of Palembang, meanwhile Suhartono et al (2021) reported the presence of Salmonella spp. that are resistant to azithromycin, tetracycline, and streptomycin in the Lamnyong and Krueng waters, Aceh.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the consumption of antibiotics as medicine has increased significantly, and their usage has grown globally [ 1 ]. Cefixime (SF) and tetracycline (TC) are two commonly used antibiotics that can act as potential antibacterial agents against many bacterial infections [ 2 ]. Due to their extensive consumption, they produce a large number of pharmaceutical residues that can easily remain in the environment.…”
Section: Introductionmentioning
confidence: 99%